1996
DOI: 10.1111/j.1570-7458.1996.tb00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitive reaction and induced resistance in rice against the Asian rice gall midge Orseolia oryzae

Abstract: Rice seedlings of the resistant variety Phalguna showed premature tillering, browning of central leaf, and tissue necrosis at the apical meristem following artificial infestation with avirulent biotype 1 of the Asian rice gall midge, Orseolia oryzae (Wood‐Mason) (Diptera: Cecidomyiidae). Tissue necrosis representing a typical hypersensitive reaction (HR), accompanied by maggot mortality, was observed within 4 days after infestation. However, reinfestation of secondary tillers subsequent to HR in primary tiller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 19 publications
1
53
0
Order By: Relevance
“…For example, HR was observed in many willow tree varieties (Salix viminalis) with resistance to the gall midge Dasineura marginemtorquens (Hoglund et al, 2005;Larsson & Wingsle, 2005). HR is also associated with wheat resistance to the Hessian fly Mayetiola destructor (Grover, 1995), rice resistance to the Asian rice gall midge Orseolia oryzae (Bentur & Kalode, 1996), peach resistance to aphids (Sauge et al, 1998), and bean resistance to the bean-pod weevil Apion godmani (Garza et al, 2001).…”
Section: Overall Categories Of Direct Defensementioning
confidence: 99%
“…For example, HR was observed in many willow tree varieties (Salix viminalis) with resistance to the gall midge Dasineura marginemtorquens (Hoglund et al, 2005;Larsson & Wingsle, 2005). HR is also associated with wheat resistance to the Hessian fly Mayetiola destructor (Grover, 1995), rice resistance to the Asian rice gall midge Orseolia oryzae (Bentur & Kalode, 1996), peach resistance to aphids (Sauge et al, 1998), and bean resistance to the bean-pod weevil Apion godmani (Garza et al, 2001).…”
Section: Overall Categories Of Direct Defensementioning
confidence: 99%
“…In more than 90% of oviposition, galls failed to initiate indicating the effectiveness of this defense by the host plant. HR has also been recognized as one of the most relevant mortality factor by which rice, wheat, and beans defend against their major herbivore pests (Shukle et al 1992;Bentur and Kalode 1996;Garza et al 2001 (2001) have now concluded that this poorly studied induced defense mechanism may have evolved very early. However, the only examples of HR against galling insects we are aware of so far come from agronomic crop plants and from some wild tropical trees and shrubs, and this does not reflect its frequency and importance in nature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, HR-like lesions were observed in willow (Salix viminalis) tree varieties with resistance to the gall midge Dasineura marginemtorquens (Hoglund et al, 2005). HR-like symptoms were also observed with wheat (Triticum aestivum) resistance to the Hessian fly Mayetiola destructor (Grover, 1995), rice (Oryza sativa) resistance to the Asian rice gall midge Orseolia oryzae (Bentur and Kalode, 1996), peach (Prunus persica) resistance to the aphid Myzus persicae (Sauge et al, 1998), and bean (Phaseolus vulgaris) resistance to the bean-pod weevil Apion godmani (Garza et al, 2001). Despite these phenotypic observations, the biological significance of ROS in plant defense against insects remains to be established, and the mechanism for ROS generation in plants upon insect attack has yet to be determined.…”
mentioning
confidence: 96%